Narrating Legends and Beliefs: The Panauti Temple as Living Cultural Heritage from Constructivist Lens - Bishwakarma, Lila Bahadur; Rajbhandari, Tejendra Prakash (Punyawati Journal, 2025)
Abstract available with full text.